1995
DOI: 10.1016/0029-7844(95)00130-j
|View full text |Cite
|
Sign up to set email alerts
|

Monoamniotic and Pseudomonoamniotic Twins: Sonographic Diagnosis, Detection of Cord Entanglement, and Obstetric Management

Abstract: Monoamniotic twin pregnancies and cord entanglement in such twins were diagnosed reliably by ultrasound. Abnormal tracings prompting cesarean delivery occurred in two of the five pregnancies with cord entanglement. Amniocentesis reflected pulmonary maturity of both twins in all pregnancies so assessed, and delivery after 32 weeks' gestation, with lung maturity, resulted in good perinatal outcomes. Statistical validity of these findings is limited by our small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 7 publications
0
64
0
1
Order By: Relevance
“…The latter difference is thought to be related not only to placental sharing, but also to the presence of inter-twin placental vascular anastomoses. Monochorionic monoamniotic (MCMA) twins account for approximately 1% of monozygotic twins with a reported incidence ranging from 1:1650 to 1:93734 live births (Aisenbrey et al, 1995;D'Alton & Simpson, 1995;Derom et al, 1988;Colburn & Pasquale, 1982;Simonsen, 1966). MCMA pregnancies are also associated with a very high risk of pregnancy loss (Ezra et al, 2005;Roqué et al, 2003).…”
mentioning
confidence: 99%
“…The latter difference is thought to be related not only to placental sharing, but also to the presence of inter-twin placental vascular anastomoses. Monochorionic monoamniotic (MCMA) twins account for approximately 1% of monozygotic twins with a reported incidence ranging from 1:1650 to 1:93734 live births (Aisenbrey et al, 1995;D'Alton & Simpson, 1995;Derom et al, 1988;Colburn & Pasquale, 1982;Simonsen, 1966). MCMA pregnancies are also associated with a very high risk of pregnancy loss (Ezra et al, 2005;Roqué et al, 2003).…”
mentioning
confidence: 99%
“…Detecting early complications, such as fetal malformations and cord entanglement in monochorionic twin pregnancies by ultrasound and doppler monitoring is important in order to improve prenatal diagnosis 15 . The risk of cord entanglement in monoamniotic twins representing adverse movements in the second trimester, increased to 40-70%.…”
Section: Figure 1 A) Umbilical Cord Entanglement During the Cesareanmentioning
confidence: 99%
“…There is no consensus regarding optimal fetal surveillance or timing of delivery. Some authors have suggested delivery after fetal lung maturity (Aisenbrey et al, 1995;Rodis et al, 1987). Others have commented that there is no advantage of prophylactic preterm delivery and have claimed that the risk of such delivery outweighs the risk of fetal death (Carr et al, 1990;Tessen & Zlatnic, 1991).…”
Section: Twin Research August 2003mentioning
confidence: 99%